STUDENTS' PERCEPTIONS OF THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN ENGLISH LANGUAGE LEARNING AT STIA LPPN PADANG - Mellati Mandasari; Yahfenel Evi Fussalam; Ridho Kurniawan (Journal Of Language Education and Development (JLed), 2024)
ABSTRACT This study aims to analyze students' perceptions of the use of Artificial Intelligence (AI) in English language learning at Sekolah Tinggi Ilmu Administrasi (STIA) Lppn Padang. In particular, it focuses on the application of ChatGPT, an AI-based chatbot developed by OpenAI, to assist students in improving their writing skills. Through surveys and interviews, data were collected from students to evaluate their experiences and perceptions of using ChatGPT. The findings reveal that while many students appreciate the support provided by AI in terms of ease of access to information, improved writing efficiency, and enhanced understanding, concerns remain regarding over-reliance on technology and potential impacts on independent learning. This research contributes to the broader discussion on integrating advanced technology into educational practices and its implications for future learning environments. Keywords: students' perceptions, Artificial Intelligence (AI), English language education